Diseño de un sistema de gestión de seguridad y salud ocupacional para la instalación y mantenimiento de fibra óptica en el sector industrial y minero - Mamani López, Julio Cesar (2017)
Works with optical fiber (installation and maintenance) are carried out in diverse scenarios such as industrial and mining, which are considered high risk. The use of fiber optics for telecommunication systems is already becoming more widespread. Therefore, dedicated measures and procedures are required to mitigate the effects of risks, hazards and their consequences, that allows the company to compliance the legislation and safety requirements. In this sense, this thesis contributes to the mitigation of these risks and hazards with the design, development and implementation of an Occupational Health and Safety Management System (OHSMS), composed of procedures that improve the conditions of workers on installation and maintenance activities for fiber optic networks in industrial and mining environments, in both underground and aerial areas. These procedures consider modern methods, Peruvian regulations (Law No. 29783 on Safety and Health at Work and its regulations) and international standards (OHSAS 18001: 2007) in the execution of these works, eliminating risk conditions and substandard acts that can to become fatal incidents and accidents, impacting to persons, equipment, materials and the environment. The methodology applicated in the present thesis is of general method divided in phases: literature review, experimental development of the OHSMS and evaluation and interpretation of results. On the other hand, consideration over Deming cycle on continuous improvement for Planning, Do, Check and Act (PDCA) are applied on the proposed OHSMS. The case study of this research considers the characteristics and conditions of the company Vías de Telecomunicaciones E.I.R.L. in the processes of optical fiber laying in industrial and mining environments. As contributions of this thesis we can highlight the development of an "Audit Check List based on Peruvian Law No. 29783", which is used to carry out an initial analysis on the safety procedures that must be performed by any company; and a " Occupational Health and Safety Management System" (OHSMS), composed of: an annual occupational safety and health program, a job training program, a safety and environmental policy, IPERC matrices for critical activities and safety work procedures. These documents, procedures, and guidelines are detailed in the thirteen procedures described in this document. For the validation of the results, was designed a mechanism called "Checklist of Guidelines", which is used for evaluation of the OHSMS considering seven guidelines. This mechanism considers the Likert scale to quantify the evaluated items. The evaluation of the company Vías de Telecomunicaciones E.I.R.L. under this mechanism, generated as result only 37.01% of accomplishment to the requirements, which is classified as "Low". A result with this qualification for any company is interpreted as the need to reformulate the current OHSMS in operation, because this OHSMS not comply with the current legislation and is probably that the workers are exposed to certain risks and hazards